The Life of the Mind - Arendt, Hannah 1906-1975 (London Harvest, 1978)
The author's final work, presented in a one-volume edition, is a rich, challenging analysis of man's mental activity, considered in terms of thinking, willing, and judging. Edited by Mary McCarthy; Indices.